In vivo models for measuring placental glutatione-stransferase (GST-P 7-7) levels: A suitable biomarker for understanding cancer pathogenesis - Noguti, Juliana; Barbisan, Luis Fernando [UNESP]; Cesar, Augusto; Seabra, Camilo Dias; Choueri, Rodrigo Brasil; Ribeiro, Daniel Araki (My University, 2012)
The Glutatione-S-transferases (GSTs) comprise a family of enzymes closely associated with the cell detoxification of xenobiotics. GSTs exist as homo- or heterodimers and have been grouped into at least seven distinct classes. The main function of GSTs is to catalyze the conjugation of reduced glutathione (GSH) to an electrophilic site of a broad range of potentially toxic and carcinogenic compounds, thereby making such compounds less dangerous and enabling their ready-excretion. Placental GST, known as GST-P 7-7, is the main isoform found in normal placental tissue and comprises 67% of the total GST concentration in this tissue. During development, GST-P 7-7 decreases in concentration and is absent in adult tissues. Interestingly, GST-P 7-7 expression has been detected in adult tissues after exposure to carcinogenic agents in several experimental test systems, being considered a reliable biomarker of exposure and susceptibility in early phases of carcinogenesis. In this article, we review a series of studies involving GST-P 7-7 expression as a suitable tool for understanding cancer pathogenesis, especially cancer risk.
Keywords: Cancer; GST-P 7-7; In vivo models; Review